JURIDICAL ANALYSIS ON CONSUMER PROTECTION IN SAFE AND HALAL FOOD DISTRIBUTION - Fifik Wiryani; Mokhammad Najih; Abdul Haris (Jurnal Dinamika Hukum, 2018)
As a Muslim majority country, it goes without saying that Indonesia protects the rights of Muslim consumers on risk free and halal food distribution. This doctrinal juridical approach aims to analyze the regulation of the safe and halal food consumers’ rights and their application to judicial decisions. The regulation of halal food distribution has provided a legal protection for the food consumers. The weakness of the regulation lies on the general criminal sanction without any specific minimum provision. A review of the court's verdict shows that the application of criminal sanction of the safe and halal food consumers’ rights violations is still inconsistent. This is an implication of the general criminal sanction which gives free space to law enforcement to apply minimum penalty. This condition causes potentially violated regulation by food business actors. Keywords: consumer protection, food distribution, judge's decision.